Genomic Screening for Malignant Hyperthermia Susceptibility - Biesecker, Leslie G (Anesthesiology, 2020)
Malignant Hyperthermia(MH) was described 60 years ago and our understanding of the clinical and pathophysiologic features of this syndrome continue to advance. MH is attributed to a genetically determined susceptibility to an abnormal skeletal muscle cell calcium flux triggered by potent inhalation anesthetics (e.g., isoflurane) or succinylcholine. Since dantrolene sodium was approved in 1979 the mortality from malignant hyperthermia dropped substantially, but remains 4-10%. The exact incidence of malignant hyperthermia reactions is unknown but may be as high as one in 25,000 anesthetics. Variants in three genes cause the susceptibility to this disorder. The RYR1 gene is most common followed by CACNA1S and STAC3. While the caffeine-halothane contracture test and the in vitro contracture test are considered the gold standards for diagnosis of susceptibility to malignant hyperthermia, there have been important advances in genetic testing. Due to these advances, it is timely for the field to consider the utility and practicability of screening for malignant hyperthermia susceptibility using genomic testing. Here we pose a simple, but bold question; what would it take to end deaths from malignant hyperthermia? We review recent advances and propose a scientific and clinical pathway toward this audacious goal to provoke discussion in the field.